Marie Paneth papers - Paneth, Marie
Correspondence, a diary, writings, reports, notes, and children's artwork chiefly documenting Paneth's therapeutic use of art in working with children who suffered traumatic experiences. Subjects include Paneth's book, Branch Street: a sociological study concerning her work with children during the bombardment of London, England, during World War II, her postwar work with children who survived German concentration camps, her years in Vienna, Austria, and Indonesia, her theories pertaining to drawing, and her art studies with Franz Cizk. Correspondents include Heinz Hartmann.
Artist, teacher, and writer. Born 1895; died 1986.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Cizk, Franz; Hartmann, Heinz, -- 1894-1970 -- Correspondence; Art; Child concentration camp inmates; Drawing; Holocaust survivors; World War, 1939-1945 -- Children -- England -- London; World War, 1939-1945 -- Concentration camps; Austria -- Social life and customs; Indonesia -- Social life and customs; Vienna (Austria) -- Social life and customs; Artists; Authors; Educators